2013
DOI: 10.1024/0300-9831/a000161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc Intake on Mental and Motor Development in Infants: A Meta-Analysis

Abstract: A systematic review and meta-analysis of available randomized controlled trials (RCTs) was conducted to evaluate the effect of zinc (Zn) intake on mental and motor development in infants. Out of 5500 studies identified through electronic searches and reference lists, 5 RCTs were selected after applying the exclusion/inclusion criteria. The influence of Zn intake on mental and motor development was considered in the overall meta-analysis. Other variables were also taken into account as possible effect modifiers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Studies relating to infants (aged 0-12 months) were excluded from this review because the systematic review and meta-analyses in infants were conducted by the research team at ULPGC and reported elsewhere. 41…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies relating to infants (aged 0-12 months) were excluded from this review because the systematic review and meta-analyses in infants were conducted by the research team at ULPGC and reported elsewhere. 41…”
Section: Search Strategymentioning
confidence: 99%
“…For the purpose of this review, studies with infant were not included (n = 356) as this has been reported elsewhere. 41 A further 1814 studies were excluded because they did not assess cognitive function outcomes or they provided insufficient data to be considered for a comparative analysis, were not conducted on healthy participants, provided zinc as a multi-micronutrient supplement or were published in a language outside the scope of this study.…”
Section: Reasons For Exclusionmentioning
confidence: 99%
“…Experimental studies have demonstrated that the cytoarchitecture of the cerebral cortex can be irreversibly disturbed in iodine deficiency, causing abnormal neuron migratory patterns that are associated with cognitive impairment in children [18]. Regarding zinc, no association was found between zinc intake and mental and motor development in infants [19]. Although no significant effects of maternal vitamin B12 supplementation were observed on cognitive development in 9-month-old infants 9, increased maternal total homocysteine levels were associated with poorer cognitive performance in some of the subdomains of Bayley Scales of Infant Development-III [20].…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane systematic review (2012) concluded that there is no significant effect of zinc intake on mental and motor development in children [34]. This was nuanced by another systematic review, published later that year, stating that the effect of zinc supplementation on cognitive function might be dependent on the dose of supplementation and the duration of the intervention [35].…”
Section: Zincmentioning
confidence: 99%